On the right to euthanasia: a conceptual approach from international human rights law - Orozco Solano, Víctor Edo (2024)
This work aims to analyze the normative and jurisprudential configuration of the right to euthanasia, based on the rulings of the European Court of Human Rights on this matter. The right to euthanasia is also distinguished from other similar terms